ORGANIZING PHYSICS LABORATORY SESSIONS BASED ON DIFFERENTIATION - Imomov Obidjon Elamonovich (Web of Journals Publishing, 2024)
This article discusses the principles of developing professional competencies in future engineers through the implementation of project-based models in differentiated approaches to physics laboratory sessions in higher education institutions.
Keywords: didactic principles, synergetic principles, cultural competence, methodology, concept, nonlinear educational trajectories, differential education, innovative education.